Breastfeeding Practices and Dietary Diversity among Infants and Young Children in Rural and Urban-Slum Populations in India: An Observational Study - Deshmukh, Urmila; Thomas, Tinku; Swaminathan, Sumathi; Kurpad, Anura (International Journal of Child Health and Nutrition, 2018)
Background: Nutritional exposures and growth in early life are linked to immediate and also to long term health outcomes. Objective: To assess infant and young child feeding (IYCF) practices using WHO-UNICEF defined indicators in rural and urban-slum populations in India. Methods: A community-based, cross-sectional study was conducted in mothers and infants up to age 24 months. Data on socio-demographics, birth history, feeding practices (WHO-UNICEF IYCF indicators), maternal weight, height, and infant’s weight, length, mid-arm, and head circumferences were collected. Results: Five hundred and two (252 rural and 250 urban-slum) mother-infant dyads were studied. Proportions of IYCF indicators in rural and urban-slum infants were: Early initiation of breastfeeding 71 and 64%; Exclusive breastfeeding under six months, 59 and 25%; Minimum acceptable diet 11 and 27% respectively. Consumption of animal-source food (other than dairy products) and vitamin-A rich fruits and vegetables was below 15%. Cesarean section [aOR, 95% CI: 2.94 (1.53, 5.65)], hospitalization of newborn [aOR, 95% CI: 6.21 (2.95, 13.16)], pre-lacteal feeding [aOR, 95% CI: 3.38 (1.77, 6.45)], needing help in breastfeeding [aOR, 95% CI: 2.15 (1.04, 4.17)], and male gender [aOR, 95% CI: 2.13 (1.15, 4.25); p<0.05 for all] were associated with delayed initiation of breastfeeding, whereas lower monthly household income [aOR, 95% CI: 2.62 (1.10, 6.25)], and younger age [aOR, 95% CI: 1.24 (1.11, 1.38); p<0.05 for both] were associated with poor dietary diversity. Conclusions: Education of optimum IYCF practices, targeting early initiation of breastfeeding, increasing meal frequency and intake of vitamin-A rich and animal-source foods need urgent attention.